PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT DAN KOMITMEN ORGANISASI PEMERINTAH DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Empiris di Desa Aji Jahe, Desa Aji Buhara dan Desa Aji Julu) - Vivi Valensya Br Karo; Arthur Simanjuntak; Mitha Christina Ginting; Lamria Sagala (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This study aims to determine the effect of apparatus competence, community participation, commitment of village government organizations on the accountability of Village Fund management in Aji Jahe, Aji Buhara and Aji Julu Villages. This type of research is causal associative research with a quantitative approach. This research was conducted in Aji Jahe, Aji Buhara and Aji Julu Villages in Karo Regency, Sumut. The population and sample in this study were 41 people. This study uses primary data obtained using a questionnaire. While the data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of SPSS 25 software. The results of this study found that apparatus competence, community participation and commitment of village government organizations have a positive and significant effect on the accountability of village fund management in Aji Jahe, Aji Buhara and Aji Julu Villages. In other results, it can be seen that simultaneously all independent variables have a significant effect on the accountability of village fund management in Aji Jahe, Aji Buhara and Aji Julu Villages.